Hydraulic stability of multi-layered sand-filled geotextile tube breakwaters under wave attack - Kriel, Herman Jacobus (Stellenbosch : Stellenbosch University, 2012)
ENGLISH ABSTRACT: Current understanding of the hydraulic stability of a stacked geotextile tube structure under wave attack is limited. Failure mechanisms that lead to instability are complicated and there is, as yet, no generic approved design method. 2D physical modelling in the large wave/current flume of the Stellenbosch University was done to test various set-up and hydraulic conditions to determine the hydraulic stability of a stacked geotextile tube structure against wave attack. Sixty-five test runs of approximately 1,000 waves each were run. Modelling was done on two different scales that had good similitude, despite the fact that the same geotextile and fill material were used in both. The results provided by the physical modelling gave wave conditions larger than anticipated for hydraulic stability. It was found that the term ―failure‖ was too loosely defined in most cases and that, depending on the definition of structure failure the severity of the wave conditions at failure increased substantially. Sliding was found to be the key failure mechanism for a structure constructed from stacked, 80% sand filled, geotextile tubes. The crest tube receives the most severe loading and is the critical tube in the structure. Structures with double tube crests were found to be negligibly more stable than structures with single tube crests, but reduce energy transmission to the leeside of the structure. Impact loading of the structure combined with wave transmission over the structure explained the wave force on the crest tube of the structure. A modified Goda (1974) method incorporating a wave reduction factor for wave transmission and an angle descriptive of the crest tube position were used. The descriptive angle was derived from results obtained from the physical modelling. The use of this method provides results that correlate well with those found in the physical modelling and with results obtained in previous research. The method has the additional advantage that it is less constrained by limitations for application than those of previous studies